Pulsed plasma rocket- developing a dynamic fission process for high specific impulse and high thrust propulsion. (August 2022) - Howe, Steven D.; Howe, Troy; Bennett, Francesca G.; Blaylock, Nathan; Jackson, Gerry; Cassibry, Jason
Abstract: The Pulsed Plasma Rocket (PPR) is an advanced nuclear propulsion concept that uses a fission-based nuclear power system to rapidly cause a phase change in a fuel projectile from solid to plasma during a pulsed cycle. To create the plasma bursts that provide thrust, a highly moderated Low Enriched Uranium (LEU) projectile can be used in combination with an unmoderated LEU barrel to preferentially heat the projectile. A short section of High Enriched Uranium (HEU) at the barrel base, along with a novel control drum mechanism, allows for controlled and rapid neutron population growth to transition into a plasma state in a fraction of a second. The PPR concept is intended to provide fast transit to and from locations such as Mars, with the engine capable of providing 100, 000 N of thrust and 5, 000s of specific impulse. The pulsed plasma rocket is a revolutionary new technology that is much more efficient than traditional rocket engines. It creates a plasma field that can be used to generate thrust, allowing spacecraft to travel much faster and farther than traditional rockets. This technology is essential for future space exploration, as it will allow us to travel to other planets and moons in the solar system.